The eastward enlargement of the eurozone : state of the art report - Michael Bolle; José Caétano; Jaakko Kiander; Vladimir Lavrač; Renzo Orsi; Hanns-Dieter Jacobsen (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
European Monetary Union (EMU) and its enlargement to prospective members in central and eastern Europe is a politically highly desired process, given that everything works out smoothly. The future eurozone will show a much higher degree of heterogeneity than now. The CEEC are in the process of transition from a planned to a market economy. Despite considerable progress during the past decade, much remains to be done in economic, social, and political terms. However, it is important to note that monetary integration is not a stand alone project, but is preceded by the EU enlargement and its obligation to adopt the acquis communautaire. Both events will be mutually reinforcing: The acquis contains numerous rules and institutions to be followed or created by the prospective members, albeit enforcement will be a problem. The success of the eastward enlargement of the eurozone depends on these institutions and, thus, increases the costs of failure. On the other hand, a successfully introduced euro in the CEEC will facilitate the whole integration process. Accession to the eurozone requires a tremendous structural adjustment in the CEEC. There are the obvious, formal requirements: the acquis, the fulfilment of the convergence criteria of the Maastricht treaty and the enlargement conditions laid down in the treaty of Copenhagen, and finally the renunciation of monetary autonomy. But these lead to more, subtle and deeper changes. Competition pressure will increase while at the same time the scope for public intervention will diminish. After all, this is believed to promote efficiency and prosperity in the CEEC, however, it may also prove to be strain at least for a certain time. Whatever the assessment of the net benefit of the eastward enlargement of the eurozone, there will be losers, in the applicant states as well as in the current members. It will be of utmost importance to realise this, to compensate for the losses or to accept them, anyway, to be aware of the political tension that may arise. ...
Keywords: 330; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Osteuropa